Feminist standpoint theory and its importance in feminist research​ - Ratna Huirem; Kathiresan Loganathan; Priyanka Patowari (Journal of Social Work Education and Practice, 2023)
Feminist research does not adhere to the set rules of looking at the world. This type of research is rather concerned with how knowledge can be produced or obtained from the oppressed section of the society in order to unveil the sufferings based on the lived experiences. The feminist standpoint model brings to light the vivid versions and solutions from the viewpoint of the participants by understanding how they view the world. The marginalization of femininity from the point of view of the lives of women can only be understood through the help of standpoint theory that places the life experiences of the oppressed groups as a vital part of the research. Feminist research aims to provide solutions to the experiences that have never been heard earlier by paving ways for empowerment, removal of inequalities and improved social guidelines. The paper digs into the pertinency of standpoint theory within the aspect of feminist research.